Developmental cell interactions in Myxococcus xanthus and the spoC locus - Shimkets, Lawrence J. (1983)
The product(s) of the Myxococcus xanthus spoC locus is required for two multicellular activities in fruiting body development, rippling and sporulation. Ripples, which are formed early in development, are spatially separated ridges of cells that move synchronously. Myxospores are heat-resistant resting cells that are formed near the end of the developmental process. To investigate the function of spoC, it was cloned in an Escherichia coli plasmid, then transferred to M. xanthus by specialized transduction with coliphage P1. The plasmid, which cannot replicate in M. xanthus, integrated into the M. xanthus chromosome, producing two copies of the spoC locus in tandem. Cells containing one copy of a mutant allele and one copy of the wild-type allele displayed the wild-type phenotype. Cells containing two different mutant alleles failed to ripple or sporulate, implying that all four independent spoC mutations are in the same gene or unit of transcription. Homozygous mutant duplications arose from constructions in which DNA from a spo(+) donor was transduced into a spoC recipient, or vice versa, at an average frequency of 14%, indicating that gene conversion was a frequent event.